2020
DOI: 10.1097/prs.0000000000006635
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Length of Postoperative Drain Use, Parenteral Opioids, Length of Stay, and Complication Rates in Patients Receiving Meshed versus Unmeshed Acellular Dermal Matrix in 194 Submuscular Tissue Expander–Based Breast Reconstructions: A Single-Surgeon Cohort Study

Abstract: Background: Studies have cited possible complications and increased fluid accumulation in implant-based breast reconstruction using acellular dermal matrix. The authors propose a novel approach, manually meshing acellular dermal matrix using a skin graft mesher before use in expander-based breast reconstruction. The authors investigated postoperative drain time, complication rates, pain, and length of hospital stay in meshed versus unmeshed acellular dermal matrix cohorts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Within the implanted thick ADM, there may be a relatively a longer process, involving the ingrowth of blood vessels and recolonization by fibroblasts, myofibroblasts, and various connective tissue free cells (lymphocytes, macrophages, granulocytes, mast cells). In addition, it has been suggested that porous ADMs provide a larger surface area of ADM/host interface, thus accelerating the integration process, and meshed ADM significantly decreased the time needed for postoperative drain (22,23). Nonetheless, in this study, ADM thickness did not affect the incidence of complications.…”
Section: Discussionmentioning
confidence: 50%
“…Within the implanted thick ADM, there may be a relatively a longer process, involving the ingrowth of blood vessels and recolonization by fibroblasts, myofibroblasts, and various connective tissue free cells (lymphocytes, macrophages, granulocytes, mast cells). In addition, it has been suggested that porous ADMs provide a larger surface area of ADM/host interface, thus accelerating the integration process, and meshed ADM significantly decreased the time needed for postoperative drain (22,23). Nonetheless, in this study, ADM thickness did not affect the incidence of complications.…”
Section: Discussionmentioning
confidence: 50%
“…Hagarty et al [25] reported that the use of meshed ADM in 192 cases in breast reconstructions involving a tissue expander was advantageous in terms of postoperative drain duration, hospitalization period, complications such as seroma, and frequency of painkiller use. In this study, the seroma rate was lower in patients who underwent DTI breast reconstruction using meshed SurgiMend than in those who underwent surgery using fenestrated SurgiMend, but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…ADM is a popular intervention to reduce the rate of CC. An RCT has found that ADM does not reduce postoperative pain [43], but another study states that meshed ADM has significantly reduced overall complications including postoperative pain [36]. Multiple studies mention the promising outcomes of ADM in the incidence of CC; however, most of these studies were short of duration.…”
Section: Management Approaches To CCmentioning
confidence: 99%
“…Due to the early formation of peri-implant fibrosis, ADM may play an important role in preventing the CC formation rather than delaying the formation [ 34 ]. In terms of the difference between the matrices, fenestrated acellular matrices are not significantly different than nonfenestrated matrices in the reduction of CC rates [ 35 ]; however, meshed acellular matrices significantly decrease the rates of minor complications including postoperative drain duration, narcotic use, and length of stay vs. unmeshed matrices [ 36 ].…”
Section: Reviewmentioning
confidence: 99%